The Relationship Between Teacher Discipline and the Role of Parents and Students' Learning Motivation at SDN Karanganyar 03 Weru Sukoharjo - Befika Fitriya Dewi; Fitri Wulandari (al-Afkar, Journal For Islamic Studies, 2024)
.  The purpose of this research is to determine the relationship between teacher discipline and the role of parents and students' learning motivation at SDN Karanganyar 03. This research uses quantitative methods with a correlation research type. The data and sources in this research were obtained from data from questionnaires and observations of students and parents. This research was carried out at SDN Karanganyar 03 class IV for the 2022/2023 academic year with a total of 10 students. Data collection techniques use questionnaires, documentation and interviews. Instrument testing was carried out using validity tests and reliability tests. The data analysis techniques used are descriptive statistics, normality test, linearity test, multicollinearity test, simple correlation analysis. Based on the results of descriptive statistical analysis, the research results showed that teacher discipline had an average of 79.26 and a percentage of 79.26% in the good category, the role of parents had an average of 79.31 and a percentage of 79.31% in the good category, and motivation to learn High class students have an average of 79.0625 and a percentage of 79.0625% in the good category. Based on the results of inferential statistical analysis, it shows that the calculated t value (4.33391) is greater (>) the t table value (1.66462) at the 5% significance level. Thus ????0 is rejected and ????1 is accepted. The research results obtained in the research are that there is a significant relationship between teacher discipline and the learning motivation of high class students at SD Negeri Karanganyar 03.